Sports selection of volley-ball players: genetic criteria to define motor endowments (information 2) - Абликова, Алиса Владимировна; Сергиенко, Леонид Прокофьевич (Slobozhanskyi Herald of Science and Sport, 2016)
Ablikovа A., Serhiyenko L. Purpose: to define genetic criteria which can be used while selecting gifted volley-ball players. Material & Methods: the study involved 50 high class volley-ball players and 50 women at the age of 20–29 years old. There were used methods of theoretical analysis and general conclusion, systematic analysis, genealogic methods of genetics, methods of dermatoglyphic and serologic analyses. Results: family gift for going in for sport was detected. At was revealed that gifted volley-ball players had peculiar finger tips prints and distribution of blood groups: the system AB0 in comparison with the total population. Conclusions: the obtained quantitative characteristics of finger dermatoglyphic, some blood groups and rhesus-factor as genetic markers of motor endowments of volley-ball players are proposed.